Study on decentralized voltage for hydropower distributed geberation for IEEE 14 bus test system - Niruben Kumar Jaya Kumar (2023)
Distribution genaration is in popularity in distribution system as an alternative power source to help supplement power and act as a voltage control of a distribution system.This project aims to identify the viability of a hydropower distribution generation as a viable voltage control in the distribution system.The test system is modeled with a 33KV Base system with 50Hz frequency since it is to emulate the characteristic of a Malaysiandistribution system.